Distribution, bioavailability and contamination assessment of mercury and arsenic in the surface sediments from the Yellow River Estuary, China. Issue 1 (2nd January 2021) - Ge, Meng; Liu, Guijian; Liu, Houqi; Liu, Yuan
Abstract: The distributions of mercury (Hg) and arsenic (As) in the surface sediments of the Yellow River Estuary (YRE) of China were investigated. The average Hg concentration (54.05 ng g −1 ) in the YRE sediments was much higher than the background, while the average As concentration (9.53 μg g −1 ) was comparable with the background. Atmospheric deposition Hg might be the major source of Hg in most studied sediments, while the point source Hg discharge might explain the relatively high levels of Hg in the specific site. The agricultural non-point source pollution and the natural sources might be the main source of As in the YRE sediments. The result of the European Community Bureau of Reference (BCR) sequential extraction experiment showed that the most hazardous fraction (F1) contributed only a small percentage of the total concentrations for both Hg and As while the fraction with low mobility and bioavailability (F4) represented the maximum composition, indicating a low risk of mobility and bioavailability for Hg and As in the sediments. In addition, multiple indices and guidelines for sediment quality assessments were used in this study, results suggested a "good state" regarding Hg and As contamination in the surface sediments from the YRE.